Investigating the Sleep-Burnout Connection and Its Impact on Health-Related Quality of Life Among Medical Registrars at a University in South Africa - Mkatazo, Nomvuyiseko Aluta (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.